Insights from computational modeling on the potential hemodynamic effects of sinus rhythm versus atrial fibrillation - Anselmino, Matteo; Scarsoglio, Stefania; Ridolfi, Luca; De Ferrari, Gaetano Maria; Saglietto, Andrea (Frontiers in Cardiovascular Medicine, 2022)
Atrial fibrillation (AF) is the most common clinical tachyarrhythmia, posing significant burden to patients, physicians and healthcare systems worldwide. With the advent of more effective rhythm control strategies, such as AF catheter ablation, an early rhythm control strategy is progressively demonstrating its superiority not only in symptoms control, but also in prognostic terms, over a standard strategy (rate control, with rhythm control reserved only to patients with refractory symptoms). This review summarizes the different impact exerted by AF on heart mechanics and systemic circulation, as well as on cerebral and coronary vascular beds, providing computational modeling-based hemodynamic insights in favour of pursuing sinus rhythm maintenance in AF patients.